(untitled) (Research, Society and Development, 2022)
Soil salinization can occur anthropogenically or secondary or as a result of natural processes such as the weathering of minerals or even the increase in capillarity of more saline groundwater in regions with lower water tables. Among the anthropogenic sources of soil salinization, industrial activities such as oil exploration, mining and shrimp farming stand out, with an emphasis on unsustainable agricultural practices. The implementation of irrigation systems in the semiarid region often promotes changes that result in the accumulation of salts on the soil surface, rise in the water table and contamination of water resources, impacting the environmental dynamics of that place. Therefore, this literature review aimed to address the main impacts related to secondary salinization and its effects on soil properties, also analyzing the cultivation in saline conditions of crops of agricultural importance and their impacts on plant development. This work was guided by a bibliographic survey that grouped important themes about secondary salinization of the soil and the cultivation of crops resistant to this type of environment. Based on the results obtained in this review, it is concluded that irrigation with low quality water has been presented as an alternative for agricultural production, especially for crops that have been shown to be resistant to saline soils and that may represent an important alternative for regions with water shortages.